1996
DOI: 10.1063/1.868876
|View full text |Cite
|
Sign up to set email alerts
|

Bifurcating jets generated with stepped and sawtooth nozzles

Abstract: A simple round jet is perturbed by attaching either a stepped or a sawtooth trailing edge that acts as a form of passive control. Flow visualization, laser Doppler anemometer, and hot-wire measurements are used to document the flow behavior in both water and air for Reynolds numbers of 7600 and 22 000, respectively. When the jet is forced, the flow bifurcates. The bifurcation requires a low forcing frequency that encourages the formation of tilted primary vortex rings with significant vorticity and axial spaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 15 publications
3
32
1
Order By: Relevance
“…Interestingly though, regardless of the inclined-section relative sharpness (at least for these two studies by the authors), cross-sections of hybrid inclined jets deduced from PIV measurements appeared to correlate well with those of bifurcated jets, especially those of Longmire and Duong [37]. However, closer inspections of the cross-stream flow visualization results indicated that this is unlikely to be the case.…”
Section: Effects Of Axial Length On Circular Notched and Hybrid Inclimentioning
confidence: 49%
See 1 more Smart Citation
“…Interestingly though, regardless of the inclined-section relative sharpness (at least for these two studies by the authors), cross-sections of hybrid inclined jets deduced from PIV measurements appeared to correlate well with those of bifurcated jets, especially those of Longmire and Duong [37]. However, closer inspections of the cross-stream flow visualization results indicated that this is unlikely to be the case.…”
Section: Effects Of Axial Length On Circular Notched and Hybrid Inclimentioning
confidence: 49%
“…A more recent study by Longmire and Duong [37] offered an interesting take on the concept of stepped nozzles. In this experimental investigation, comparisons were conducted between a conventional stepped nozzle and one which was based on a "sawtooth" design, at Reynolds numbers of Re = 7600 and 22,000, as well as under unforced and forced flow conditions.…”
Section: Circular Modified Nozzle Jetsmentioning
confidence: 99%
“…This is due to the unsteady minijet injections placed on the upper side. The periodic excitation may accelerate shear layer growth [19]. At x * = 1.0, the shear layer …”
Section: Flow Structure Developmentmentioning
confidence: 99%
“…Longmire & Duong [19] introduced the combination of both asymmetric passive technique and axial periodic excitation to manipulate a round jet by attaching a stepped trailing edge and a speaker upstream of the jet plenum. The vortex ring in the jet developed an inclined component and became asymmetrical, resulting in significant enhancement of entrainment and spreading.…”
Section: Introductionmentioning
confidence: 99%
“…Liner stability analyses have shown that two types of dominant modes characterize the large-scale flow structures of the near-field of a jet, namely, varicose and helical modes, and diffusion or mixing is effectively controlled through these modes. It is well known that a complex jet comprises a combination of these modes (2), (3) . For example, a flapping mode comprises a pair of helical modes with the same frequency and same amplitude.…”
Section: Introductionmentioning
confidence: 99%